Time of the adult emergence and natural mortality of the cotton boll weevil - Ramalho, Francisco de Sousa; Silva, José Roberto Bezerra (Pesquisa Agropecuaria Brasileira, 1993)
The time of the adult emergence and the natural mortality of the eggs, larvae, pupae and pre-emergent adults of the boll weevil (Anthonomus grandis Boheman) were studied in the "Várzea Alegre" Farm at Ingá, PB, Brazil, in 1989 and 1990 cotton seasons. Each experimental unit consisted of one emergence cage. Two hundred and four hundred damaged squares (with egg punctures) with open and yellow bracteas in 1989 and 1990 seasons, respectivelly, were placed on the soil surface under the emergence cage. The study showed that: (1) the emergence of boll weevil adults occurs from 6:00 up to 16:00 hours, with a significant peak from 7:00 up to 10:00 hours, (2) the real mortality of the boll weevil is 35.05%, (3) desiccation, parasitism and predation are the most important causes of the boll weevil mortality within cotton squares, and (4) the natural mortality of the A. grandis is highest in the larval fase.
Keywords: insects; Anthonomus grandis; parasitism; predation; desiccation; egg inviability